THE CONCEPT OF FACIAL CONTRAFORS AND PRIKUS. - Tursunboyeva Nigina; Gadayev A.M (Лучшие интеллектуальные исследования, 2023)
Annotation. This article delves into the intricate concepts of facial contrafors and prikus, exploring their relevance and significance in various fields. Through a comprehensive literature analysis, we aim to shed light on the existing knowledge, methodologies employed, and the implications of these concepts. The study employs a systematic approach in the methods section to investigate facial contrafors and prikus, presenting the results in a detailed manner. The discussion section critically examines the findings, providing insights into the broader implications. Conclusions and suggestions for future research conclude the article, offering a roadmap for further exploration.